Efficacy and Safety of Late Bleb Needling to Prolong Post-Trabeculectomy Hypotensive Effect - S. Yu. Petrov; D. M. Safonova (Oftalʹmologiâ, 2019)
Purpose. To assess the efficacy and safety of late bleb needling to prolong the hypotensive effect after glaucoma surgery. Patients and Methods. The study included 130 patients (130 eyes) with IOP decompensation after trabeculectomy. The patients were divided into 3 groups: cystous blebs (50 eyes), incapsulated blebs (50 eyes) and biomicroscopically absent blebs that reveal intraocular fluid collections under the sclera flap during optical coherence tomography (30 eyes). All patients underwent tonometry, visometry and bleb hyperemia assessment. Results. Patients with cystous blebs showed a mean IOP reduction from 25.4 ± 3.2 mm Hg to 12.7 ± 4.5 mm Hg the day after needling. During the follow up period the mean IOP level showed a minimal fluctuation within the bounds of 13–15 mm Hg. Incapsulated blebs demonstrated a reduction from 28.9 ± 6.3 to 15.1 ± 4.3 mm Hg in the course of the first day. The following IOP fluctuations remained within a higher range, than in Group 1: 15.9–18.3 mm Hg. IOP dynamics in the visually absent bleb group had its specificts: the initial procedure led to a transient IOP increase from 24.6 ± 4.7 mm Hg to 27,6 ± 3,5 mm Hg, followed by a reduction within the first day to the level 19.4 ± 3.1 mm Hg, with further IOP fluctuations during the follow up period staying withing the range of 14.6–15.8 mm Hg. Performing bleb needling to restore trabeculectomy hypotensive efficacy had a total surgical success in 100 % patients with cystous blebs, that were formed as a result of conjunctival-scleral lesions. Incapsulated bleb needling had a 74 % total success rate and visually absent blebs with intraocular fluid collections under the flap had a 90 % total success rate within the 6 month follow up period. Conclusion. The study shows high efficacy of late needling of different blebs as an invasive measure of restoring post-trabeculectomy hypotensive effect.